O PROGRAMA MARANHÃO PROFISSIONAL: qualificar para o desemprego? - HOLANDA, Felipe Macedo de (2017)
This research carries out a political evaluation of the Integrated Professional Education Program of Maranhão State, Brazil – Programa Maranhão Profissional, an ambitious strategy launched by the Government of Roseana Sarney (PMDB) in May 2011, which aimed to qualify about four hundred thousand workers in the four-year period until 2014, especially to supply qualified workers to large investment projects of a primary-export nature, planned or being installed in the State of Maranhão. The theoretical-historical contextualization refers to the Program as an active labor market policy in a context of productive restructuring, a process characterized by the flexibilization of labor relations, both externally (under more precarious and unstable forms of employment), as well as on the internal level (customized production, under the Toytist paradigm), demanding a new profile of workers' qualification, multifunctional, in which relational skills are valued more than the specialization by functions existing in the previous paradigm. The trajectory of the experiences of professional qualification in Brazil indicates, as a long-durée structure, the disarticulation with regular education and also the permanence of a social assistance character, rather than pedagogical one. In the post-1990 period, despite repeated government attempts to integrate professional education into regular education, the lack of financial resources and ambiguities brought by the attempt to reconcile antagonistic interests prevented progress in this direction. The political evaluation of the Professional Maranhão Program shows, firstly, an inadequacy of its institutional design in confrontation to the conditionalities of the National Qualification Program - PNQ and PRONATEC. Among these dislocations, which severely limited the possibilities of success to the Program, mention is made to the lack of mobilization of the State and Municipal Councils of Employment and also the disregard, in the design of the Program, of the necessary actions of intermediation with the labor market and also the designing of systems of Monitoring, evaluation and follow-up of graduates. It is important to mention, in addition, the conflict of interests of qualifying institutions with presence in the Deliberative Councils of the Program. The methodology of projection of demand for skilled workers configures indeed an institutional advance of the Program, but it is nevertheless called attention to errors of dimensioning the necessary supply of qualifications and also in the budgeting of the planned actions. There are also contradictions in the focus of the program, by privileging, on the one hand, the market demand for qualified workers, and prioritizing, on the other hand, populations in a situation of social vulnerability, in addition to offering courses with reduced hours and disarticulated of market´s needs. Finally, attention is drawn to the passive vision of development revealed in the evaluation of the implicit economic and social development strategy that guides the Program. The consequence of which is the inexistence of a long-term investment strategy capable of guiding the qualification strategy to supporting the overcoming of the labor-saving primary-export model, which would require the consolidation of productive chains capable of generating employment, income and fiscal productivity, in activities oriented to the domestic market, such as the agri-food sector.